2022
DOI: 10.1002/cft2.20160
|View full text |Cite
|
Sign up to set email alerts
|

An examination of turfgrass species use on golf course putting greens

Abstract: Core Ideas Golf course superintendents were surveyed to create maps delineating turfgrass species use on putting greens. Creeping bentgrass was used on putting greens across the vast majority of the continental United States in 2021. This dataset provides a baseline for future studies examining changes in golf course species use on putting greens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
4
1
0
Order By: Relevance
“…Again, these findings were similar to those of Brosnan et al. (2022), which also found that creeping bentgrass was the dominate putting surface in the transition zone. Stakeholders in the warm‐season turfgrass zone would benefit from the works produced by Brosnan et al.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Again, these findings were similar to those of Brosnan et al. (2022), which also found that creeping bentgrass was the dominate putting surface in the transition zone. Stakeholders in the warm‐season turfgrass zone would benefit from the works produced by Brosnan et al.…”
Section: Resultssupporting
confidence: 91%
“…These findings are similar to results produced by Brosnan et al. (2022) in which the vast majority of survey respondents identified creeping bentgrass as the dominant turfgrass on putting greens across the United States. Extension specialists or stakeholders in the cool‐season turfgrass zone would benefit most from research conducted by Cain et al.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…An advantage of using seashore paspalum is its ability to tolerate saline/sodic soils and poor water quality often found in reclaimed water and coastal environments (i.e., Southeast region and California) (Duncan and Carrow 2000). Shaddox et al (2022) reported that 87% of all reclaimed water use on golf courses occurs in the Southeast and Southwest regions.…”
Section: Resultsmentioning
confidence: 99%